Efflux pumps as an additional source of resistance to trichothecenes in Fusarium proliferatum and Fusarium oxysporum isolates - Popiel, Delfina (J Appl Genet, 2019)
Role of efflux-mediated toxin resistance to trichothecenes is known in trichothecene-producing species. However, the role of trichothecene efflux pump homologues in non-producing fusaria such as F. oxysporum and F. proliferatum was not investigated in detail. Analysis of the homologues of trichothecene efflux pump from multiple fungal species allowed us to uncover and catalogue functional gene copies of conserved structure. Putative Tri12 candidates in Fusarium oxysporum and F. proliferatum were characterised via expression profiling in response to different trigger compounds, providing supporting evidence for role of Tri12 homologues in the resistance to trichothecenes. Our analysis of Tri12 phylogeny also suggests that efflux-mediated trichothecene resistance is likely to predate the divergence of Trichoderma and Fusarium species. On the regulatory level, we posit that the increased tolerance of trichothecenes by F. oxysporum is possibly related to the decoupling of Tri12 homologue expression from pH, due to the deletion of PACC/RIM101 transcription factor binding site in its promoter region. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13353-019-00501-2) contains supplementary material, which is available to authorized users.